Continuing Transformation: Śrī Nāth, His Gurus and His Devotees in a Timeless World - van der Velde, Paul (Religions, 2023)
Śrī Nāth is one of the most important images of Krishna being worshipped at the temple of Nathdwara in Rajasthan. His devotees consider him to be a living god, he appears in their dreams, and according to their sayings they are in direct contact with him. Śrī Nāth, originally a local deity, is equated with the major Hindu god Krishna. However, while Krishna may be one of the most important gods in India, he is also ambiguous through his acts and words, if not bluntly unreliable. This double nature of Krishna is reflected in the cult of Śrī Nāth. There is an interesting interaction between Śrī Nāth (implying Krishna himself), the main gurus of his cult, i.e., Vallabha (Vallabhācārya) and the latter’s son and main successor Viṭṭhalnāth and his devoted disciples. At times, Śrī Nāth feels the need to stick to the official Brahmanical cult of the temple rituals, on other occasions, there is no problem in transgressing any given official rule. The same is true for the primary teachers, who are often put on par with Krishna himself or one of the celestials closely connected to him. Additionally, the disciples can apparently do anything in their frenzies. All of this reinforces the idea that this entire cult belongs to another world (alaukik). It is part of the everyday world (laukik) of Hindu India, but meanwhile, each and every rule can be ignored if the supernatural breaks through. Even the distinction between Hinduism and Islam at times simply does not seem to be of importance anymore. Muslims can become addicted to the passionate love for Krishna through the form of Śrī Nāth, so it is sometimes stated. Each and every partaker in the cult may share the visions of the initiated devotee, at times even without proper initiation. This all adds to the experience of the supermundane and supernatural in this particular cult.